2022
DOI: 10.1039/d2cc01796b
|View full text |Cite
|
Sign up to set email alerts
|

High entropy metal chalcogenides: synthesis, properties, applications and future directions

Abstract: Metal oxides, sulphides, selenides and tellurides have routinely been investigated and utilised for a wide range of applications, in particular in the areas of energy (photovoltaic, thermoelectric) and catalysis (thermocatalysis,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 88 publications
1
64
0
Order By: Relevance
“…Lewis's research group has extensively explored the versatility of metal xanthates and thiocarbamates for the phase-pure preparation of various exotic multinary metal sulfides. [14][15][16][17] Similarly, Revaprasadu et al have also investigated the suitability of xanthates and thiocarbamates for the preparation of several important nanosized metal sulfides. [18][19][20] However, a thorough literature study has revealed that xanthates have not been explored for the preparation of technologically important Cu 2 GeS 3 nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…Lewis's research group has extensively explored the versatility of metal xanthates and thiocarbamates for the phase-pure preparation of various exotic multinary metal sulfides. [14][15][16][17] Similarly, Revaprasadu et al have also investigated the suitability of xanthates and thiocarbamates for the preparation of several important nanosized metal sulfides. [18][19][20] However, a thorough literature study has revealed that xanthates have not been explored for the preparation of technologically important Cu 2 GeS 3 nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…One such method to synthesize phase pure multinary metal sulfides employing metal xanthates and thiocarbamates has been explored and established by Lewis [33][34][35] and Revaprasadu's group. [36][37][38] These metal xanthates being single source molecular precursors (SSMPs) have advantages over the normal metal salt precursors for the synthesis of ternary ZIS NCs.…”
Section: Introductionmentioning
confidence: 99%
“…35,36 The novel class of multifunctional materials known as transition metal telluride has gained a lot of interest recently owing its high electrical conductivity, varying valence states, and unique electrochemical characteristics, with comparison to the oxides, hydroxides, sulfides, and selenide despite the higher (electrical conductivity) Te ions in comparison with O/S/Se ions and it has weak metal-Te ionic bonds in host lattice structures. 37 However, (transition metal tellurides) generally struggled with large particle agglomeration and volume fluctuation throughout the prolonged cycling processes, leading to pulverization and morphological deterioration, fast capacity decline, and a shorter cycle life. However, the above concern problem has been improved by taking the appropriate concentration of the precursor in the synthesis of metal telluride leading to the change in morphology of the materials.…”
Section: Introductionmentioning
confidence: 99%